Seven scuticociliates (Protozoa, Ciliophora) from Alabama, USA, with descriptions of two parasitic species isolated from a freshwater mussel Potamilus purpuratus - Pan, Xuming (European Journal of Taxonomy, 2016)
Isolates of Mesanophrys cf. carcini Small & Lynn in Aescht, 2001 and Parauronema cf. longum Song, 1995 infected a freshwater mussel (bleufer, Potamilus purpuratus (Lamarck, 1819)) collected from Chewacla Creek, Auburn, Alabama, USA. Free-living specimens of Metanophrys similis (Song, Shang, Chen & Ma, 2002) 2002, Uronema marinum Dujardin, 1841, Uronemita filificum Kahl, 1931, Pleuronema setigerum Calkins, 1902 and Pseudocohnilembus hargisi Evans & Thompson, 1964, were collected from estuarine waters near Orange beach, Alabama. Based on observations of living and silver-impregnated cells, we provide redescriptions as well as comparisons with original descriptions for the seven species. We also comment on the geographic distributions of known populations of these aquatic ciliate species and provide a table reporting some aquatic scuticociliates of the eastern US Gulf Coast.